IMPACTS OF CIRCULAR ECONOMY ON THE DEVELOPMENT OF ECOTOURISM ASSOCIATED WITH ORGANIC AGRICULTURE - Nguyen Van Nhung; Nguyen Thi Bich Thuy (HUIT Journal of Science, 2025)
The article examines the impact of circular economy on the development of ecotourism associated with organic agriculture in the Southeast region. The results of the study identified 5 influencing factors, including: (1) Waste management and recycling (WMR); (2) Use of renewable energy (REU); (3) Natural resource conservation (NRC); (4) Green Technology Application (GTA) and (5) Sustainability and Traceability Certification (SCT). Based on the research results, the author proposes solutions to strengthen the application of the circular economy model to promote the sustainable development of ecotourism combined with organic agriculture.